Unified in Our Diversity to Address Health Disparities Among Asian Americans, Native Hawaiians, and Pacific Islanders (Mary Ann Liebert, 2022)
The COVID-19 pandemic disproportionately impacted Asian Americans, Native Hawaiians, and Pacific Islanders (AA/NHPIs) in the United States. AA/NHPIs have historically been subjected to discrimination, which was exacerbated by the pandemic. To bring attention to their unique concerns, an AA/NHPI Interest Group of the National Institutes of Health Community Engagement Alliance Against COVID-19 Disparities (CEAL) was formed. This article highlights major concerns raised by the Interest Group: The pervasive and arbitrary practice of data aggregation by public health agencies and health-related researchers, the lack of culturally responsive services in the context of cultural safety, and leadership underrepresentation.